MORFOLOGI DAN HISTOKIMIA KELENJAR MANDIBULARIS WALET LINCHI (Collocalia linchi) SELAMA SATU MUSIM BERBIAK DAN BERSARANG (Morphological and Histochemical Properties of Mandibular Glands of the Cave Swiflets (Collocalia linchi) During Reproductive and Nesting Period) - Savitri Novelina (Jurnal Kedokteran Hewan, 2010)
The aimed of present study is to investigate the morphological and histochemical of mandibular glands of the cave swiflet (Collocalia linchi). The study used 24 adult wallet linchii paired mandibular gland located in the ventral of the mandible. They were ovoid in form and whitish in color. The gland consisted of mucous acinar cells and waspositive with PAS but negative with AB (pH 2,5). The result suggested that the acinar cells of the mandibular gland contained only neutral mucopolysaccharides and no acid mucopolysaccharides. Staining with 7 biotinylated lectins, Con-A, DBA, WGA, RCA, PNA, SBA, and UEA which represent carbohydrates with galactosa-, Nacetylgalactosamine,sialic acid, 2-5 N-acetylglucosamine, á-D- mannose, showed various positive reaction in the secretion of the acinar cells depends on the type of lectin and sampling period. The result suggested possiblecorrelation between receptor gonadal hormone with the activity of reproductive and nesting period of walet linchi.Keywords: lectin, Collocalia linchi,salivary gland.